“I Think, Therefore the Cinema Exists”: Relationships Between Film and Philosophy According to Juliette Cerf - Demby, Łucja (Media - Culture - Social Communication, 2021)
This article presents various aspects of the relationship between cinema and philosophy in the theoretical works of Juliette Cerf, which have not yet been discussed in Polish film studies. These two fields have been related since the beginning of the cinema, and the problem itself was analysed by such figures as Henri Bergson. His philosophical thought has also influenced contemporary film theory (Gilles Deleuze). The author of the article specifies and presents several issues dealt with by Cerf, including: philosophers talking about the cinema; the cinema talking about philosophers; the cinema creating its own philosophy; the cinema teaching philosophy. The main thesis of the article is that the cinema should not recreate the existing philosophies; instead, it should create its own philosophy based on its specific means of expression. The author also presents the concept of filmosophy, which is widespread in Western literature, yet not well-known in Poland, in which film is treated as an auxiliary to the teaching of academic philosophy.